Occurrence of antibiotic resistant C. jejuni and E. coli in wild birds, chickens, humans, and the environment in Malay villages, Kedah, Malaysia - Mohamed, Mohamed-Yousif Ibrahim; Abu, Jalila; Abdul Aziz, Saleha; Zakaria, Zunita; Abdul Rashid Khan; Habib, Ihab (Czech Academy of Agricultural Sciences, 2022)
Foodborne pathogens have become a major concern not only due to the diseases they cause, but also because of the rise of antibiotic resistant strains in human and animals. The purposes of this study were to determine the occurrence of Campylobacter jejuni and Escherichia coli and their antibiotic resistance profiles in wild birds, chickens, humans, and the environment in Malay villages in Malaysia. Three Malay villages in Kota Setar, Kedah were chosen. Three hundred nine (309) samples were collected in this study including wild birds (38), chickens (71), humans (47), and the environment (153). Subsequently, the C. jejuni and E coli isolates were tested against antibiotics using the disc diffusion method. Campylobacter jejuni was found positive in 17 (37.8%) flies and 8 (11.3%) chickens. Also, E. coli was found positive in 89.4% of human, 47.4% of bird, 44 62% of chicken and in 71.2% of the environmental samples. Ten antibiotics were used to determine the susceptibility of the isolates. Eighty four percent (84%) of C. jejuni and 100% of E. coli isolates were found to show resistance towards at least one antibiotic. The isolates showed high resistance to cefpodoxime and tetracycline.